The improved antitumor efficacy of continuous intratumoral chemotherapy with cisplatin-loaded implants for the treatment of sarcoma 180 tumor-bearing mice - Gao, Li (Drug Deliv, 2019)
Cisplatin is the most commonly used antitumor drug in the chemotherapy of a variety of malignancies. However, the severe side effects and drug resistance limit its clinical application. The aim of this study was to develop PLGA-based cisplatin-loaded implants and evaluate the antitumor efficacy of continuous intratumoral chemotherapy with the implants. The cisplatin-loaded implants were prepared by the direct compression method and characterized regarding drug content, micromorphology, in vitro and in vivo drug release profiles. Furthermore, the antitumor activity of the implants was conducted in sarcoma 180 tumor-bearing mice. The SEM images showed smooth surface of the implants and the mean drug content of the tested implants was (37.7% ± 0.5%, w/w). Both in vitro and in vivo release profiles of the implants were characterized by initial burst release followed by the sustained-release of cisplatin. Intratumoral implantation of the cisplatin-loaded implants could effectively inhibit the tumor growth. Additionally, intratumoral chemotherapy with the implants significantly reduced the systemic toxicity compared with intravenous injection of cisplatin. It is worth noting that an increase in the dose of the implants led to a higher tumor suppression rate without additional systemic toxicity. These results demonstrated that cisplatin-loaded implants enhanced the antitumor efficacy and reduced the dose-related side effects in sarcoma 180 tumor-bearing mice.